2005
DOI: 10.1016/j.jacc.2005.05.085
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Effects of Statins: Benefit Beyond Cholesterol Reduction?

Abstract: The pleiotropic effects of statins do not seem to contribute an additional cardiovascular risk reduction benefit beyond that expected from the degree of LDL-C lowering observed in other trials that primarily lowered LDL-C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
192
4
11

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(212 citation statements)
references
References 93 publications
5
192
4
11
Order By: Relevance
“…Lowering LDL-C levels has been shown to reduce the risk of CVD events in several interventional and epidemiologic studies [1113,3739]; that holds for both statin [40,41] and non-statin therapies [42,43]. The evolocumab CV outcomes trial, Further Cardiovascular Outcomes Research with PCSK9 Inhibition in Subjects With Elevated Risk (FOURIER) [16], demonstrated that the addition of evolocumab to SoC is associated with a reduced incidence of major CVD events.…”
Section: Methodsmentioning
confidence: 99%
“…Lowering LDL-C levels has been shown to reduce the risk of CVD events in several interventional and epidemiologic studies [1113,3739]; that holds for both statin [40,41] and non-statin therapies [42,43]. The evolocumab CV outcomes trial, Further Cardiovascular Outcomes Research with PCSK9 Inhibition in Subjects With Elevated Risk (FOURIER) [16], demonstrated that the addition of evolocumab to SoC is associated with a reduced incidence of major CVD events.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, lowering of oxLDL levels by statins might contribute to some of the cholesteroldependent effects of statins. Furthermore, data from meta-analysis of lipid-lowering trials suggest that lipid modification alone accounts for the clinical benefits associated with statin therapy [18]. However, both the level of efficacy and early treatment benefits as a result of statin therapy have so far been greater than the beneficial effects of non-statin lipid-lowering therapies.…”
Section: Clinical Trials With Statinsmentioning
confidence: 99%
“…Ridker et al (90) observed that patients whose statin therapy reduced LDL-cholesterol to <70 mg/dl (<1·81 mM/dl), had a reduced rate of recurrent myocardial infarction or death from coronary events (2·7 events per 100 person-years), than individuals whose statin therapy did not reach this goal (4·0 events per 100 person-years). However, it has also been demonstrated non-statin therapy (diet, bile acid sequesterants and ileal bypass surgery) reduced CHD risk equally to that of statins, with each 1 % reduction in LDLcholesterol corresponding to a 1 % decrease in CHD risk (10) . Statins can also be used in combination with drugs such as Ezetimbibe, which targets NPC1L1 to lower cholesterol absorption.…”
Section: Pharmacological Interventionmentioning
confidence: 99%
“…It is likely that these alterations play a role in the accumulation of LDL-cholesterol and disease pathogenesis. The accumulation of plasma cholesterol can also be moderated by diet, while pharmaceutical and pre-and probiotic administration have largely been associated with reduced LDLcholesterol levels and CVD risk (9)(10)(11)(12)(13) .…”
mentioning
confidence: 99%